Effects of elevated atmosphere CO2 and temperature on the morphology, structure and thermal properties of starch granules and their relationship to cooked rice quality. (March 2021) - Jing, Liquan; Chen, Chen; Hu, Shaowu; Dong, Shupeng; Pan, Yue; Wang, Yunxia; Lai, Shangkun; Wang, Yulong; Yang, Lianxin
Abstract: The rapidly increasing atmospheric CO2 is accompanied by global warming. However, the effects of the elevated CO2 concentration (EC) and/or air temperature (ET) on starch morphology, structure and thermal properties which considerably contribute to the taste of cooked rice have not been reported to date. Therefore, a field experiment using a temperature/free-air CO2 enrichment facility was conducted with EC (+200 ppm) and/or ET (+1 °C) treatments from 2014 to 2016. The surface area of starch granules and proportion of large starch granules were significantly increased by EC and ET, but the most significant increases of 3.4% and 5.9%, respectively, were induced by the combined treatment. EC did not change the crystalline type but altered the order structure of starch molecules: EC averagely decreased the ratios of 1045/1022 and 1022/995 cm −1 by 2.6% and 3.3% respectively, however, significantly increased the crystallinity by 4%. For most cases, EC significantly increased the gelatinization temperature and pasting viscosity of starch, decreased setback, enthalpy and protein content and eventually improved rice taste. Results of correlation analysis suggested that EC affected the thermal properties of starch and the taste of cooked rice mainly by improving the size and molecule order structure of starch granules. Small and few significant ET and EC × ET effects were detected, indicating that the EC influence will be predominant in future climate. These findings will help in improving rice palatability and developing the starch industry. Graphical abstract: Graphical abstract. Summary scheme of elevated CO2 and temperature on starch physiochemical properties and taste of cooked rice. ↑, increase; ↓, decrease; temperature, crop canopy temperature; CO2 concentration, atmospheric CO2 concentration; 1045/1022 cm −1, a parameter in ATR-FTIR spectra; Gelatinization temperature, averaged across the onset, peak and conclusion temperatures in DSC; Pasting viscosity, breakdown and setback, three parameters in RVA profile. Image 1 Highlights: Elevated CO2 (EC) and temperature (ET) notably increased the starch granule size. EC slightly decreased the 1045/1022 cm −1 of starch under open field conditions. However, EC greatly enhanced the crystallinity degree of starch granules. Changes in these indexes may mainly contribute to the improved taste of cooked rice. Only few significant ET and EC × ET effects on starch and rice taste were detected.